2016
DOI: 10.1352/1944-7558-121.5.398
|View full text |Cite
|
Sign up to set email alerts
|

Engaging Communities in Identifying Local Strategies for Expanding Integrated Employment During and After High School

Abstract: Amidst decades of attention directed toward improving employment outcomes for people with intellectual and developmental disabilities (IDD), few efforts have been made to engage communities in identifying local solutions for expanding integrated employment opportunities. We examined the implementation and outcomes of "community conversation" events held in 6 geographically and economically diverse locales. Each event used an asset-based dialogue approach called the World Café ( Brown & Isaacs, 2005 ) to solici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 37 publications
2
35
0
Order By: Relevance
“…In 2015, the employment-population rate for people without disabilities in the U.S. was 65%, but only 20% of individuals with developmental disabilities between the ages of 18 and 34 indicated that they currently had community employment, despite 59% of individuals in this age range without a job in the community reporting that they would like one (National Core Indicators, 2015;United States Department of Labor, 2016). There are several potential reasons for this disparity, including employment discrimination in certain fields (Houtenville & Kalargyrou, 2015), lack of a marketable skillset, social skill deficits, insufficient available supports (Test, Smith, & Carter, 2014), low expectations from family and educators (Doren, Gau, & Lindstrom, 2012), and lack of work and internship experiences (Carter et al, 2016;Carter et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In 2015, the employment-population rate for people without disabilities in the U.S. was 65%, but only 20% of individuals with developmental disabilities between the ages of 18 and 34 indicated that they currently had community employment, despite 59% of individuals in this age range without a job in the community reporting that they would like one (National Core Indicators, 2015;United States Department of Labor, 2016). There are several potential reasons for this disparity, including employment discrimination in certain fields (Houtenville & Kalargyrou, 2015), lack of a marketable skillset, social skill deficits, insufficient available supports (Test, Smith, & Carter, 2014), low expectations from family and educators (Doren, Gau, & Lindstrom, 2012), and lack of work and internship experiences (Carter et al, 2016;Carter et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…An asset-based approach has been applied extensively in the areas of community development (Dolezal & Burns, 2015;Johnson Butterfield, Yeneabat, & Moxley, 2016;Wu & Pearce, 2014); education (Chikoko, Naicker, & Mthiyane, 2015;Missingham, 2017;Ssewamala, Sperber, Zimmerman, & Karimli, 2010); social welfare (Carter et al, 2016;Culp, 2017;Soaita, Searle, McKee, & Moore, 2016); and business (Fisher et al, 2009;Tracey, O'Sullivan, Lane, Guy, & Courtemanche, 2017). For example, the basis of an assetbased approach within the field of community development is to create 'community' by focusing on assets available within the community and connecting these, rather than focusing on shortcomings and deficits (Kretzmann & McKnight, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Expectations for employment were uneven among families, educators, and other professionals; existing policies inconsistently aimed toward integrated employment; the availability of strong professional development was limited; accessible resources and information were difficult to find; pursuit of integrated employment was not incentivized; our commitment to employment first did not always penetrate practice; silos were more common than sustained collaboration; and stories of struggles were more common than stories of success. These barriers emerged as recurring themes in our conversations with stakeholders, in the community gatherings we held across the state (Bumble, Carter, McMillan, & Manikas, in press;, and in our surveys of parents and educators (Bethune, Carter, & O'Quinn, 2016;Blustein, Carter, & McMillan, 2016).…”
Section: The Tennessee Contextmentioning
confidence: 98%
“…Early in our project, we launched a study aimed at understanding the views of more than 2,400 parents across our state on employment for their daughters and sons with IDD: their post-school expectations, the factors that shape those expectations, and the concerns they hold (Blustein et al, 2016;Gilson, Bethune, Carter, & McMillan, in press). We learned that a large proportion of parents (83%) placed considerable importance on part-or full-time employment in the community for their child in the early years after leaving high school.…”
Section: Elevating Expectationsmentioning
confidence: 99%
See 1 more Smart Citation